Flow in VR: A study on the relationships between preconditions, experience and continued use - Hassan Lobna; Jylhä Henrietta; Sjöblom Max; Hamari Juho (United States, 2022)
Flow is characterized as an autotelic experience where action and awareness merge, there is high concentration on task and little attention is paid to time or self. It is believed that VR has a powerful affordance for inducing the flow state, as VR is, at least anecdotally, a technology that transports users to immersive realities, which can facilitate flow. However, VR imposes usability challenges that may inhibit flow. This research investigates flow in VR and its characteristics, determinants and outcomes through a survey (n = 681) and Structural Equation Modeling (SEM). The results indicate that flow in VR is positively association with intentions to continue VR use and longer VR sessions.
Proceedings of the 53rd Annual Hawaii International Conference on System Sciences